ANALISIS EKSEGESIS LUKAS 16:1-9 DAN IMPLIKASI SEMANTIK MANAJEMEN RISIKO BAGI MUTU LAYANAN PENDIDIKAN DI STT ARASTAMAR WAMENA - Ivo Sastri Rukua; Sensius Amon Karlau (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2026)
This study aims to discover the semantic content of words and language in the Gospel of Luke 16:1-9 through analytical steps. This effort is motivated by the interest of risk mitigation to improve the quality of services at STT Arastamar Wamena which has not yet reached the level set in the Development Master Plan (RIP) document. Qualitative methods accompanied by a library approach underpin the steps of diachronic, synchronic analysis, and critical thinking. This is an elaborative effort supported by literature in the form of Greek interlinear, commentaries, and scientific articles on risk management and the quality of educational services. This effort brings out the semantic implication to conclude that the Gospel of Luke 16:1-9 emphasizes the importance of identifying risks related to loss of control of resources and analyzing needs based on risk evaluation. This effort aims to calculate the impact and options through risk mitigation for resource reallocation and relationship building actions. Various efforts culminate in optimizing service quality with a smart attitude based on integrity.